The effect of phosphodiesterase-5 inhibitors on the alveolar blood fl ow in the pulmonary graft - P. K. Yablonskiy; O. N. Reznik; A. E. Skvortsov; V. E. Milehin (Трансплантология (Москва))
Lung transplantation – an effective way to radical surgical treatment of chronic lung disease in the terminal stage. The use of drugs with extending effect on vascular smooth musculature of the pulmonary circulatory system, prior to conservation and assessment of the functional state of the microvasculature in the postreperfusion period may result in improved clinical outcomes of such operations and increase the duration of the functioning of the lung transplant in the body of the recipient.Fifty four animals were used (German Field Pig, 32,3±0,6 kg, male). Forty two animals (donors and recipients) were divided into three groups according to the method of conservation. Orthogonally polarized spectral video microscopy (OPSVM) was applied for estimation the parameters of microcirculation.Injection of a phosphodiesterase-5 (PDE-5) inhibitor into the pulmonary trunk at 20 min before conservation significantly increases the total length of open alveolar capillaries per field (486,3±258,1 mkm in comparison to the initial 240,8±127,9 mkm; p<0,001) and the index of capillary blood flow of the alveoli (515,0 in comparison to the initial 249,2 mkm/mkm2; p<0,001), also the increase of the mean diameter of the alveoli was found (91,2±52,3 mkm in comparison to the initial 85,1±41,5 mkm; p<0,05).The use of PDE-5 inhibitor at 20 min before the start of perfusion of lung transplant with conservation solution improves the oxygenizing ability of the transplanted lung. OPSVM is a reliable method for assessing and monitoring the parameters of microcirculation of lung tissue in vivo.